When doctors share visit notes with patients: a study of patient and doctor perceptions of documentation errors, safety opportunities and the patient–doctor relationship. Issue 4 (18th May 2016) - Bell, Sigall K; Mejilla, Roanne; Anselmo, Melissa; Darer, Jonathan D; Elmore, Joann G; Leveille, Suzanne; Ngo, Long; Ralston, James D; Delbanco, Tom; Walker, Jan
Abstract : Background: Patient advocates and safety experts encourage adoption of transparent health records, but sceptics worry that shared notes may offend patients, erode trust or promote defensive medicine. As electronic health records disseminate, such disparate views fuel policy debates about risks and benefits of sharing visit notes with patients through portals. Methods: Presurveys and postsurveys from 99 volunteer doctors at three US sites who participated in OpenNotes and postsurveys from 4592 patients who read at least one note and submitted a survey. Results: Patients read notes to be better informed and because they were curious; about a third read them to check accuracy. In total, 7% (331) of patients reported contacting their doctor's office about their note. Of these, 29% perceived an error, and 85% were satisfied with its resolution. Nearly all patients reported feeling better (37%) or the same (62%) about their doctor. Patients who were older (>63), male, non-white, had fair/poor self-reported health or had less formal education were more likely to report feeling better about their doctor. Among doctors, 26% anticipated documentation errors, and 44% thought patients would disagree with notes. After a year, 53% believed patient satisfaction increased, and 51% thought patients trusted them more. None reported ordering more tests or referrals. Conclusions: Despite concerns about errors, offending language or defensive practice, transparent notes overall did not harm the patient–doctor relationship. Rather, doctors and patients perceived relational benefits. Traditionally more vulnerable populations—non-white, those with poorer self-reported health and those with fewer years of formal education—may be particularly likely to feel better about their doctor after reading their notes. Further informing debate about OpenNotes, the findings suggest transparent records may improve patient satisfaction, trust and safety.